Memory characteristics of capacitors with poly-GaAs floating gates - Roh, I. P.; Kang, N. S.; Shin, S. H.; Oh, Y. T.; Kim, K. B.; Song, J. D.; Song, Y. H. (INST ENGINEERING TECHNOLOGY-IET, 2016)
The memory characteristics of a capacitor with polycrystalline gallium arsenide (poly-GaAs) as a floating gate material have been evaluated, and compared with a capacitor using poly-silicon (poly-Si). The poly-GaAs film with thickness of 100 nm was successfully grown on silicon at 250 degrees C, using an arsenide beam flux, in a molecular beam epitaxy chamber. Based on the optical and electrical evaluation, this film appeared to have obvious poly-GaAs. Here, the measured the memory window by comparing it to a conventional device with a poly-Si floating gate, which showed it to have approximately twice the value of the poly-Si. Based on these results, poly-GaAs floating material can be considered to be a candidate for a wider memory window in scaled two-dimensional flash memory.